A new allele for aluminium tolerance gene in barley (Hordeum vulgare L.). (December 2016) - Ma, Yanling; Li, Chengdao; Ryan, Peter; Shabala, Sergey; You, Jianfeng; Liu, Jie; Liu, Chunji; Zhou, Meixue
Abstract Background Aluminium (Al) toxicity is the main factor limiting the crop production in acid soils and barley (Hordeum vulgare L.) is one of the most Al-sensitive of the small-grained cereals. The major gene for Al tolerance in barley isHvAACT1 (HvMATE ) on chromosome 4H which encodes a multidrug and toxic compound extrusion (MATE) protein. The HvAACT1 protein facilitates the Al-activated release of citrate from root apices which protects the growing cells and enables root elongation to continue. A 1 kb transposable element-like insert in the 5' untranslated region (UTR) ofHvAACT1 is associated with increased gene expression and tolerance and a PCR-based marker is available to score for this insertion. Results We screened a wide range of barley genotypes for Al tolerance and identified a moderately tolerant Chinese genotype named CXHKSL which did not show the typical allele in the 5' UTR ofHvAACT1 associated with tolerance. We investigated the mechanism of Al tolerance in CXHKSL and concluded it also relies on the Al-activated release of citrate from roots. Quantitative trait loci (QTL) analysis of double haploid lines generated with CXHKSL and the Al-sensitive variety Gairdner mapped the tolerance locus to the same region asHvAACT1 on chromosome 4H. Conclusions Our results show that the Chinese barley genotype CXHKSL possesses a novel allele of the major Al tolerance geneHvAACT1 .